Marvels in the muck : life in the salt marshes - Wechsler, Doug. (Honesdale, Pa. : Boyds Mills Press, 2008)
Wildlife photographs and text reveal the secrets of salt marshes, where fish, crabs, turtles, shrimp, and a variety of birds, including bald eagles, egrets, and osprey, rely on a handful of plant species that grow in the coastal wetlands that buffer the impact of hurricanes and require defending before they disappear.
Includes bibliographical references (p. 47) and index.
4.9
5-8
Keywords: Salt marsh ecology -- Juvenile literature; Salt marshes -- Juvenile literature; Salt marsh ecology; Salt marshes; Marshes; Salt marsh ecology